Elementary statistics in social research - Levin, Jack (Pearson/Allyn & Bacon, 2004)
Includes index; Why the social researcher uses statistics -- Organizing the data -- Measures of central tendency -- Measures of variability -- Probability and the normal curve -- Samples and populations -- Testing differences between means -- Analysis of variance -- Nonparametric tests of significance -- Correlation -- Regression analysis -- Nonparametric measures of correlation -- Applying statistical procedures to research problems